Tonkin - Moncay - Catholiques chinois de la mission du père grand... - Uncredited photographer. (Wikimedia Commons, 1945)
Carte postale ancienne issue de Wikimedia Commons. Titre: Tonkin - Moncay - Catholiques chinois de la mission du père grand Pierre à Chizan. A postcard depicting Chinese members of the Roman Catholic Church in the Tonkinese city of Móng Cái, Hi Ninh Province.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église